(untitled) (Indian Journal of Nematology, 2024)
Root-knot nematode (Meloidogyne incognita) is a major threat for polyhouse growers and cause great losses under protected cultivation. To reduce the use of pesticides in poly-houses and to promote the crop production, an eco-friendly management trail was conducted with different combinations of physical method (hot water treatment), organic amendments (tea waste, tobacco churi, poultry manure, water hyacinth leaf powder, lantana leaf powder and neem cake) and bio-agents (Paecilomyces lilacinus and Trichoderma harzianum). The treatment combinations were used as soil application before sowing against Meloidogyne incognita infecting cucumber in poly-house. All the combined treatments significantly reduced nematode reproduction and enhanced plant growth parameters as compared to untreated check. Maximum yield was obtained with combination of Hot water + Tobacco churi + Paecilomyces lilacinus (3.865 kg/plant) followed by Hot water + Tea waste + Paecilomyces lilacinus (3.690 kg/plant) and Hot water + Tobacco churi + Trichoderma harzianum (3.491 kg/plant) as compared to untreated check (0.983 kg/plant).